Analisis Hukum Islam Terhadap Kearifan Lokal Penetapan Jadwal Adzan: Studi Kasus Datar Putukrejo Loceret Nganjuk Jawa Timur - Moh. Faizur Rohman; Agus Solikin (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2021)
Abstract: Adhan, which is a sign of the entry of prayer time, is usually held at the beginning of time. Different things happened in Datar, Putukrejo, Loceret, Nganjuk, East Java where the call to prayer was not done at the beginning of time, but according to the schedule set by the local kiai or village kiai. In line with that, this article is the result of studies that have been carried out at that location using qualitative research methods and data collection techniques, namely through interviews and observations. Meanwhile, the data analysis used is descriptive inductive analysis method with conclusion drawing approach. Based on the explanation of the research that has been carried out, it is concluded that the village Kiai in determining the adhan's schedule by integrating the fiqh prayer time with local wisdom in order to obtain harmony. The purpose of determining the schedule for the call to prayer is to form the character of the importance of congregational prayers in the life of the congregation they lead.